IoT and Retail Management: A Bibliometric Review of Research Contributions and Opportunities - Judijanto, Loso; Nasaruddin, Nasaruddin; Syam, Andi Wahyuni (West Science Interdisciplinary Studies, 2025)
The integration of the Internet of Things (IoT) in retail management and supply chain operations has transformed business processes by enabling real-time data collection, automation, and data-driven decision-making. This study conducts a bibliometric analysis using Scopus-indexed literature and VOSviewer to map research contributions, key themes, and emerging trends at the intersection of IoT and retail management. The analysis identifies inventory management, supply chain transparency, automation, and AI-driven analytics as dominant research areas, with growing interest in blockchain-enhanced security, sustainability, and predictive analytics. Citation and co-authorship analyses highlight key influential studies and international collaboration networks, with India, China, and the United States emerging as major research hubs. Despite advancements, challenges remain in IoT security, interoperability, ethical considerations, and regulatory frameworks, necessitating further research on 5G-enabled IoT, edge computing, and resilient supply chains. This study provides a comprehensive overview of IoT-driven retail research, offering valuable insights for academics, industry professionals, and policymakers to drive innovation and efficiency in the digital retail landscape.